2009
DOI: 10.1021/es900990d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of C60 Aggregates toward Mammalian Cells: Role of Tetrahydrofuran (THF) Decomposition

Abstract: C60 fullerene is a promising material due to its unique physiochemical properties. However, previous studies have reported that colloidal aggregates of C60 (nC60) produce toxicity in fish and human cell cultures. The preparation method of the nC60 raises questions as to whether the observed effects stem from the fullerenes themselves or from the organic solvents used during the preparation of the suspensions. In this paper we set out to elucidate the mechanism by which tetrahydrofuran (THF) treatment to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 30 publications
0
39
0
4
Order By: Relevance
“…Toxicological properties of metallic NPs are difficult to evaluate because toxicity is dependant on both the nanoparticulate form and the toxic metal ions which can be released by the NPs [4,5]. In addition, it has been found that the organic compounds used in NPs' synthesis can induce by themselves toxic effects [6]. For these reasons, it has been emphasized that NPs' toxicity is complex and many toxicological aspects still remain to be further investigated [7].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicological properties of metallic NPs are difficult to evaluate because toxicity is dependant on both the nanoparticulate form and the toxic metal ions which can be released by the NPs [4,5]. In addition, it has been found that the organic compounds used in NPs' synthesis can induce by themselves toxic effects [6]. For these reasons, it has been emphasized that NPs' toxicity is complex and many toxicological aspects still remain to be further investigated [7].…”
Section: Introductionmentioning
confidence: 99%
“…At least four factors confound assessments of toxicity. First, it is now recognized that tetrahydrofuran (THF) used in nC 60 preparation generates toxic derivatives (13,22,29). Unless these derivatives and trace THF are removed, observed toxicity cannot be ascribed to nC 60 alone.…”
mentioning
confidence: 99%
“…Reports that fullerenes exhibited toxicity toward various fi sh [320,321] have been discounted by other authors [322] and attributed to the presence of a tetrahydrofuran bioproduct introduced during fullerene preparation [323] .…”
Section: Nanotoxicologymentioning
confidence: 99%